Primary Osteosarcoma of the Breast with Extensive Chondroid Matrix in a Teenager Female Patient: The Paradoxical Diagnosis in Breast Mastopathy - Yahaya, James Joseph; Odida, Michael (International Medical Case Reports Journal, 2020)
Non-epithelial tumors of the breast are extremely rare and have an incidence of less than 1%. The most common non-epithelial breast tumor is the phyllodes tumor (PT), which accounts for 61%. Primary osteosarcomas of the breast contribute up to only 12.5% of all breast sarcomas. In young females, osteosarcomas are extremely rare, especially in those without a previous history of primary bone osteosarcoma. A case of a 16-year old female with primary osteosarcoma of the breast (POB) with extensive chondroid matrix involving the left breast is herein presented.
Keywords: Osteosarcoma; Breast; Chondroid Matrix